Factors associated with COVID-19 vaccination coverage in hypertensive patients with Omicron infection in Shanghai, China - Kongbo Zhu; Shaolei Ma; Hui Chen; Jianfeng Xie; Dan Huang; Genshan Ma; Yingzi Huang (Taylor & Francis Group, 2023)
ABSTRACTThe potential future burden of COVID-19 is determined by the level of susceptibility of the population to infection. The protective effect provided by those previously infected diminishes over several months, while individuals with mixed immunity have the highest degree and persistence of protection. This study aimed to clarify the vaccination status of COVID-19 patients with hypertension and to analyze the characteristics and risk factors of non-vaccinated patients to protect this vulnerable population in the future. The study ultimately enrolled 4576 hypertensive patients with Omicron infection from April 6, 2022, to May 15, 2022. Among them, 3556 patients (77.7%) had received at least one dose of vaccine, and 2058 patients (45.0%) received a booster dose. In the multivariate logistic analysis, male (OR 1.328, 95% CI 1.138-1.550, p < .001), age (60-69 years vs.18-49 years) (OR 0.348, 95% CI 0.270-0.448, p < .001), age (≥70 years vs.18-49 years) (OR 0.130, 95% CI 0.100-0.169, p < .001), diabetes mellitus (OR 0.553, 95% CI 0.463-0.661, p < .001), chronic pulmonary diseases (OR 0.474, 95% CI 0.260-0.863, p = .015), chronic kidney disease (OR 0.177, 95% CI 0.076-0.410, p < .001), and cancer (OR 0.225, 95% CI 0.094-0.535, p = .001) were associated with vaccinated status. The vaccine coverage rate, especially the booster vaccine, was low for hypertensive patients with Omicron infection. Females, increasing age, and coexisting chronic diseases were associated with more inadequate vaccine coverage in hypertensive COVID-19 patients. Targeted interventions are required to address the under-vaccination of diverse hypertensive populations.